(untitled) (Vietnam Journal of Community Medicine, 2025)
Aim: To initially determine the value of preterm birth prediction of transvaginal ultrasound cervical angle from 22 to 28 week of single pregnant women at Ninh Bình Obstetrics and Pediatrics Hospital. Subject and method: This prospective study is performed from february 2024 to October 2024. Results: The medianpregnant women age at entry was 30,22±6,6 years. Most patients had normal BMI (82,6%). We found that about 13,2% woman gave birth before 37 weeks.Uterocervical angle is valuable inpredicting preterm birth: pregnantwomen with a cervical angle ≥ 120° were at risk of preterm birth